Color Dependence on Thickness in Topaz Crystal from Brazil - Waldemar Bonventi Jr; Sadao Isotani; Antonio Roberto Pereira Albuquerque (Advances in Condensed Matter Physics)
It is well known that crystals of topaz from the Eastern Brazilian Pegmatite Province may turn blue by the irradiation with 60Co gamma rays followed by heat treatment. Also, it is known that the sensation of color changes with the thickness of these crystals. The dependence of the color, given by 1931 CIE chromaticity coordinates, with the thickness of the crystal was analyzed. The absorbance used in the calculation of these coordinates was given by the sum of Gaussian lines. The parameters of these lines were determined through the decomposition of the optical absorption spectra in the ultraviolet and visible regions. The decomposition revealed several lines, whose assignment was made considering studies in spodumene and beryl crystals and highly accurate quantum mechanical calculations. The transmittance becomes very narrow with increasing thickness, and the CIE chromaticity coordinates converge to the borderline of the CIE Chromaticity Diagram at the wavelength of maximum transmittance. Furthermore, the purity of color increases with increasing thickness, and the dominant wavelength reaches the wavelength of maximum transmittance.